2005
DOI: 10.1207/s15327108ijap1504_3
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Conflict Detection in Air Traffic Control

Abstract: Experienced air traffic controllers and naïve college students participated in 2 experiments we conducted to test a hypothesis that controllers evaluate potential conflicts between aircraft in a hierarchical manner, comparing altitudes first for vertical separation, then extrapolating aircraft trajectories for lateral separation, and finally performing speed-distance computations for longitudinal separation. The results clearly support the hypothesis and imply that controller workload in terms of time pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 22 publications
9
78
0
Order By: Relevance
“…A previous study by Rantenan and Nunes [27] has suggested speed as a confounding factor to conflict or intercept angles and the ability to detect a conflict. It was indicated in their research that increasing the speed differential between converging objects increased the temporal error, resulting in a lower accuracy.…”
Section: Speed Variationsmentioning
confidence: 96%
See 3 more Smart Citations
“…A previous study by Rantenan and Nunes [27] has suggested speed as a confounding factor to conflict or intercept angles and the ability to detect a conflict. It was indicated in their research that increasing the speed differential between converging objects increased the temporal error, resulting in a lower accuracy.…”
Section: Speed Variationsmentioning
confidence: 96%
“…Previous research on sector complexity showed that the aircraft intercept angle [27,28,29], speed [27] and horizontal proximity [3,16] are some of the variables that are responsible for the sector complexity. The goal of the present study is to systematically analyze the properties of the SSD due to changes in the sector design.…”
Section: Sector Complexity Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that controllers indeed mind their time and regulate their workload by employing a set of strategies that are more economical in a demanding situation than under lighter workload (Sperandio, 1978). Furthermore, Rantanen and Nunes (2005) showed that controllers tended to opt for the quickest and least effortful solutions in determining possible conflicts between pairs of aircraft, exhibiting time management with a definitely conservative bias.…”
mentioning
confidence: 99%